PEMBINAAAN ORANG TUA DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI MTS KECAMATAN MALANGKE - Fathudin Ali (JIEBAR : Journal of Islamic Education: Basic and Applied Research, 2022)
This study aims to describe the guidance of parents of MTs students. in Malangke District in instilling character. This study uses a qualitative research that uses a pedagogical approach. Sources of data are primary data from parents, school principals, PAI teachers through interviews, while secondary data is taken from documents related to research. The instrument used in data collection is the researcher himself whose function is to determine and select informants as data sources, analyze data, interpret data, and instruments in collecting data are observation, interviews, and documentation. The results of the research and analysis concluded that in parenting in the formation of the character of MTs. Malangke 1) The pattern of parents in coaching in instilling character a. MTs. Cappasolo, the parenting style used by the community is a democratic pattern. B. MTs. Tokke, the parenting style used by the community is an authoritarian pattern, 2) The basic development of religion in MTs. Cappasolo and MTs. Tokke applied by parents in Malangke sub-district tends to be the same, the way to instill character and character at home is to set an example. 3) Many things can hinder the formation of character so that students do not show character such as education level, cultural environment, age, socioeconomic level.